Sosialisasi Protokol Kesehatan dalam Mencegah Penularan Covid-19 di Kelurahan Bina Widya Kota Pekanbaru - Rickha Octavia; Denni Anggraini; Adriani Susanty; Rahma Dona; Melzi Octaviani (Jurnal Health Sains, 2021)
COVID-19 cases in Riau Province are still showing a significant increase in numbers. This is due to the activities and mobility of the people of Riau Province who are very much outside the house. Problems in the community, among others, are still many who do not understand the prevention of COVID-19 transmission, including the importance of using masks when out of the house, the importance of personal hygiene, hand washing with soap, and pyshical distancing. The habit of implementing clean and healthy living behaviors is not easy, it requires understanding and motivation from individuals so that each individual is more disciplined in applying them. The purpose of this research is to increase people's knowledge about COVID-19 through leafleat media. The method used is qualitative method. Pretest the community to get an early overview of the understanding of health protocols in preventing the transmission of COVID-19. The results of the posttest questionnaire showed an increase in people's knowledge from not understanding to understanding and very understanding. This is because the measurement of knowledge is done by providing complete information about COVID-19 and its prevention through leaflet media that is very effective in improving one's knowledge. The conclusion of socialization research that has been conducted on November 29, 2020 at RW 09 RT 03 Bina Widya Village, Panam Pekanbaru Riau can be seen that there is an increase in public knowledge after this activity, thus adding to the public's insight on how to prevent the transmission of covid-19 and what foods can be consumed during the current pandemic in order to improve the immune system or immune system.